Non-Native Listeners’ Use of Information in Parsing Ambiguous Casual Speech - Natasha Warner; Daniel Brenner; Benjamin V. Tucker; Mirjam Ernestus (Languages)
During conversation, speakers produce reduced speech, and this can create homophones: ‘we were’ and ‘we’re’ can both be realized as [ɚ], and ‘he was’ and ‘he’s’ can be realized as [ɨz]. We investigate the types of information non-native listeners (Dutch L1-English L2) use to perceive the tense of such verbs, making comparisons with previous results from native listeners. The Dutch listeners were almost as successful as natives (average percentage correct for ‘is’/’was’ in the most accurate condition: 81% for Dutch, 88% for natives). The two groups showed many of the same patterns, indicating that both make strong use of whatever acoustic information is available in the signal, even if it is heavily reduced. The Dutch listeners showed one crucial difference: a minimal amount of context around the target, just enough to signal speech rate, did not help Dutch listeners to recover the longer forms, i.e., was/were, from reduced pronunciations. Only the full utterance context (containing syntactic/semantic information such as ‘yesterday’ or another tensed verb) helped Dutch listeners to recover from reduction. They were not able to adjust their criteria based on the surrounding speech rate as native listeners were. This study contributes to understanding how L2 learners parse information from spontaneous speech in a World Englishes setting with inputs from multiple dialects.